1985
DOI: 10.1287/mnsc.31.12.1533
|View full text |Cite
|
Sign up to set email alerts
|

Branch and Bound Experiments in Convex Nonlinear Integer Programming

Abstract: The branch and bound principle has long been established as an effective computational tool for solving mixed integer linear programming problems. This paper investigates the computational feasibility of branch and bound methods in solving convex nonlinear integer programming problems. The efficiency of a branch and bound method often depends on the rules used for selecting the branching variables and branching nodes. Among others, the concepts of pseudo-costs and estimations are implemented in selecting these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
198
0
14

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(212 citation statements)
references
References 10 publications
0
198
0
14
Order By: Relevance
“…Finally, the third dice has also 58.3% probability of beating the first one. The linear GDP formulation of this problem is shown in (11), and it is formulated as minimization of the number of outcomes in which dice n + 1 beats dice n (instead of maximizing the number of outcomes in which dice n beats dice n + 1).…”
Section: Design Of Nontransitive Dice (Dice)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the third dice has also 58.3% probability of beating the first one. The linear GDP formulation of this problem is shown in (11), and it is formulated as minimization of the number of outcomes in which dice n + 1 beats dice n (instead of maximizing the number of outcomes in which dice n beats dice n + 1).…”
Section: Design Of Nontransitive Dice (Dice)mentioning
confidence: 99%
“…Problem (12) has two main difference with (11). The first one is that the second disjunction of (11) is formulated as an MILP constraint, the third global constraint in (12).…”
Section: Design Of Nontransitive Dice Hybrid Gdp-minlp (Diceh)mentioning
confidence: 99%
“…Solution strategies explicitly addressing mixed-integer nonlinear programs (MINLPs) have appeared rather sporadically in the literature and initially dealt mostly with problems that are convex when integrality restrictions are dropped and/or contain nonlinearities that are quadratic [24,22,16,23,10,6,7,5]. A few recent works have indicated that the application of deterministic branchand-bound algorithms to the global optimization of general classes of MINLPs is promising [30,37,12,36].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this approach was experimented with in [63]. The Branch-andBound Algorithm for mixed-integer nonlinear programming has been implemented as MINLP-BB [88], with continuous nonlinear-programming subproblem relax-ations solved with the active-set solver filterSQP and also as SBB, with associated subproblems solved with any of CONOPT, SNOPT and MINOS.…”
Section: General Algorithmsmentioning
confidence: 99%